Inovasi Layanan Uji Kompetensi ASN Berbasis Digital Melalui Pendekatan Design Thinking dan Business Model Canvas - Ravendra Syahinda Lubis; Mahendra Wardhana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to develop an innovative competency assessment service for civil servants (Aparatur Sipil Negara/ASN) through the formulation of a new Business Model Canvas (BMC) based on a Design Thinking approach at the Competency Assessment Unit of the Regional Civil Service Agency (BKD) of East Java Province. The study is motivated by several tangible problems in the implementation of assessment services, including delays in the distribution of competency test results, limited access for ASN to detailed and transparent assessment information, and the low effectiveness of post-assessment feedback as a basis for competency development. Through the stages of empathize, define, ideate, prototype, and test, this research explores users’ actual needs by conducting in-depth interviews with UPT leaders, assessors, and ASN participants, developing empathy maps and user personas, and formulating core problems using the Point of View and How Might We approaches. The ideation process generates proposals for a more responsive service model, including the provision of a real-time digital dashboard, specific and structured feedback, the integration of post-assessment consultation sessions, and the strengthening of online service access. The study results in a redesigned BMC featuring a value proposition centered on transparency, digitalization, and continuous support, changes in service channels through interactive digital platforms, expanded customer relationships through mentoring and training, and updates to key resources and activities encompassing the development of a digital assessment information system and enhanced assessor capacity. Validation through Focus Group Discussions indicates that the proposed BMC is considered relevant and feasible for implementation, although it still requires adjustments to standard operating procedures, strengthening of human resource capacity, and support from digital infrastructure. Overall, this study demonstrates that the Design Thinking approach is effective in generating adaptive and user-centered public service business model innovations, contributing to bureaucratic transformation toward a more transparent, integrated, and responsive ASN competency assessment service.